Association between environmental exposures and granulomatosis with polyangiitis in Canterbury, New Zealand. Issue 1 (December 2015) - Stamp, Lisa; Chapman, Peter; Francis, Janine; Beckert, Lutz; Frampton, Christopher; Watts, Richard; O'Donnell, John
Abstract Introduction Granulomatosis with polyangiitis (GPA) is a rare systemic vasculitis. While aetiology is unknown the prominent respiratory involvement suggests inhaled antigens may be involved. The aim of this study was to identify environmental risk factors associated with GPA in Canterbury, New Zealand. Methods A case-controlled study was undertaken. All GPA cases fulfilled American College of Rheumatology (ACR), Chapel Hill Consensus Criteria (CHCC) or the European Medicines Agency (EMA) criteria. Each case was gender matched with four controls - 2 musculoskeletal (osteoarthritis or fracture) and 2 respiratory (asthma or chronic obstructive pulmonary disease). One musculoskeletal control and one respiratory control were age matched with the case at the time of the interview (interview) and the remaining two controls were age matched at the time their case experienced the first symptom of vasculitis (index). A structured questionnaire to assess potential environmental agents was administered without blinding for case/control status. Data were analyzed using conditional logistic regression to allow for the individual matching of cases and controls to assess for association between environmental factors and GPA. Results 49 cases and 196 controls were recruited. 53 % were male and the mean ± standard deviation (SD) age of the cases was 64.9 ± 12.4 years, interview controls 65.1 ± 12.4.years and index controls 53.9 ± 14.5 years. Any reported exposure to dust (specifically silica and grain dust) was associated with GPA, odds ratio (OR) 3.6 (95 % confidence interval (CI); 1.5–8.3, p  = 0.003). Occupation as a farm worker was associated with GPA OR 3.43 (1.5–7.5, p  = 0.002). Specific gardening activities were associated with GPA including digging (OR 3.2; 1.4–7.0;p  = 0.003), mowing (OR 2.7; 1.3–5.8;p  = 0.008) and planting (OR 2.6; 1.2–5.5;p  = 0.013). Conclusion We have replicated findings from northern hemisphere studies identifying dust exposure as well as farm exposure as risk factors for the development of GPA. We have shown activities associated with exposure to inhaled antigens, in particular those related to farming or gardening activities may increase the risk of GPA.